Severe hemolysis flare of refractory autoimmune hemolytic anemia with positive complement component C3d responsive to Iptacopan with cyclophosphamide and prednisone: a case report - Yawen Zhang; Yuemin Gong; Guangsheng He (Hematology)
Objectives: Autoimmune hemolytic anemia (AIHA) is characterized by autoimmune-mediated destruction of erythrocytes. Both AIHA and Evans syndrome are rare, manifesting a severe clinical course, high relapse rate, and potentially fatal outcomes. Refractory AIHA shows poor responsiveness to multiple treatment regimens, and there is still a lack of effective treatment regimens for serious hemolytic episodes.Methods: Three refractory AIHA cases with a positive complement component C3d and hemolytic flare were treated with the oral factor B inhibitor ptacopan in conjunction with cyclophosphamide and prednisone.Results: After treatment with iptacopan plus cyclophosphamide and prednisone, all three patients showed a rapid increase in Hb levels, a decrease in reticulocyte proportion, and a significant reduction in hemolysis manifestations (Lower LDH level and unconjugated bilirubin).Conclusion: Three refractory cases of AIHA showed good therapeutic efficacy after treatment with iptacopan combined with cyclophosphamide and prednisone. These cases provide a potentially effective treatment option for severe hemolytic episodes in refractory AIHA.